2014
DOI: 10.1038/ncomms4038
|View full text |Cite
|
Sign up to set email alerts
|

A nanocomposite superstructure of metal oxides with effective charge transfer interfaces

Abstract: The alignment of nanoparticle building blocks into ordered superstructures is one of the key topics in modern colloid and material chemistry. Metal oxide mesocrystals are superstructures of assembled nanoparticles of metal oxides and have potentially tunable electronic, optical and magnetic properties, which would be useful for applications ranging from catalysis to optoelectronics. Here we report a facile and general approach for synthesizing metal oxide mesocrystals and developing them into new nanocomposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
132
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(139 citation statements)
references
References 51 publications
(46 reference statements)
7
132
0
Order By: Relevance
“…This is an indication of substitution of Ni (ionic radius: 0.69 Å) with Zn (ionic radius: 0.74 Å) 3) and formation of the SEM morphology of the 72000 seconds (20 hrs) as-milled sample and the isothermally-heated (Argon ow) 1800 seconds milled Zn-NiO mixtures are depicted in Fig. 5(a) and 5(b), (c) respectively.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…This is an indication of substitution of Ni (ionic radius: 0.69 Å) with Zn (ionic radius: 0.74 Å) 3) and formation of the SEM morphology of the 72000 seconds (20 hrs) as-milled sample and the isothermally-heated (Argon ow) 1800 seconds milled Zn-NiO mixtures are depicted in Fig. 5(a) and 5(b), (c) respectively.…”
Section: Resultsmentioning
confidence: 87%
“…The coordination environment of the Zn 2+ sites in ZnO is suitable for nickel ions (Ni 2+ ) and this is the reason why NiO and ZnO form a solid solution. [1][2][3] The resulting complex structure depends on the x value. To the best of our knowledge, work on the solid state synthesis of such structures is quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…In general condition, anatase TiO 2 crystallite grows with the preferential exposure of {101} facet with a lower surface energy, which leads to the formation of tetragonal bipyramidal TiO 2 nanocrystals. It was reported that fluorine-containing species can favor the preferential exposure of {001} facet of anatase and thus the formation of TiO 2 nanoplate [6,12,21]. TS20 and TS40 without regular TiO 2 crystal shape show mullein-like morphology as shown in clearly shows an amorphous covering on an exposed crystallographic plane of TiO 2 crystallite, which confirms the formation of core-shell microstructure.…”
Section: Resultsmentioning
confidence: 64%
“…Moreover, TiO 2 absorbs UV light that is the tiny portion of solar spectrum but has meager response to visible light due to a wide band gap of TiO 2 [6,7]. Fortunately, many novel approaches like doping with impurities [8][9][10], noble metal deposition [11,12], sensitizing with narrow band gap absorption materials [13,14] and hydrogenation process [15,16] have been found to be effective in enabling visible light absorption, while several inventive techniques such as heterostructuring with other semiconductors [17,18], integrating with carbon nanostructures [19,20], designing with exposed reactive facets [12,21] and hierarchical morphologies [22,23] have been developed to improve structural stability and charge carrier separation kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…The samples were synthesized with some modifications according to the previous reports [22][23][24]. A precursor solution containing TiF 4 , H 2 O, NH 4 NO 3 , and NH 4 F (molar ratio = 1:503.4:4.9:2.4) was prepared, and were placed on a silicon wafer to form a thin layer.…”
Section: Preparation Of Nh 4 Tiofmentioning
confidence: 99%